3C strategy for inverters in parallel operation achieving an equal current distribution - Wu, Tsai-Fu; Chen, Yu-Kai; Huang, Yong-Heh (IEEE transactions on industrial electronics (1982), 2000)
A circular chain control (3C) strategy for inverters in parallel operation is presented in the paper. In the proposed inverter system, all the modules have the same circuit configuration, and each module includes an inner current loop and an outer voltage loop control. A proportional-integral controller is adopted as the inner current loop controller to expedite the dynamic response, while an H/sup /spl infin// robust controller is adopted to reach the robustness of the multimodule inverter system and to reduce possible interactive effects among inverters. With the 3C strategy, the modules are in circular chain connection and each module has an inner current loop control to track the inductor current of its previous module, achieving an equal current distribution. Simulation results of two-module and a three-module inverter systems with different kinds of loads and with modular discrepancy have demonstrated the feasibility of the proposed control scheme. Hardware measurements are also presented to verify the theoretical discussion.